Gender-Based Wage Differences: The Effects of Occupation and Job Segregation in Israel - Gattiker, Urs; Cohen, Aaron (Relations industrielles / Industrial Relations, 1997)
This article reports on an analysis of gender differences in the process governing salary disparity between typically female occupations and typically male occupations. The research surveyed 771 white collar employees. The findings indicate that choice of occupation does affect income disparity. This study provides evidence of pay discrimination against men in predominantly female occupations and against women in female- and male-dominated positions. In contrast to North American studies, women did not experience a positive effect by being employed in the public sector, nor did either of the genders working in larger organizations. The implications of the findings for the generalizability of human capital, structural and institutional theories explaining wage disparity in a cross-national context are discussed.